The influence of health The education using the Ludo game on teenagers' knowledge about bullying at SMA Muhammadiyah 3 Palembang - Ranti Ayu Kartika; Ayu Dekawaty; Suzanna Suzanna (Masker Medika, 2024)
ABSTRAK